Nano-phytoremediation technologies for groundwater contaminates emerging research and opportunities - Chaudhary, Khushboo, 1989- (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
"This book explores phytoremediation and some experimental methods used in life science laboratories. It also examines various heavy metals and non-metals and their effect on remedial approaches"--